Characterization of methanol metabolism genes and plant growth-promoting traits in bacteria from the rice (Oryza sativa) rhizosphere - KAVYA, T; SINGH, GEETA; GOVINDASAMY, VENKADASAMY; SUSHMITHA, C H; J, SUSHMITHA (The Indian Journal of Agricultural Sciences, 2025)
Rice (Oryza sativa L.), a dominant cereal crop is a major contributor of greenhouse gas methane emissions. The present study was carried out during 2023–2024 at ICAR-Indian Agricultural Research Institute, New Delhi to evaluate six methylotrophic bacteria isolated from the rice rhizosphere for their methanol carbon use efficiency and plant growth-promoting characteristics. Amplification of three methane metabolism genes, namely mmoX, pmoA and mxaF; and 16S rRNA gene sequencing, were identified as methylotrophs Bacillus rugosus strain MB1, Bacillus subtilis strain MB2, Priestia aryabhattai strain MB3, Rhizobium pusense strain MB4, Priestia megaterium strain MB5, and Sphingobium spp. strain MB6. Their methanol use efficiency expressed as specific respiration was in the range from from 0.009–0.063 mg of CO2/µg of protein. Their plant growth-promoting (PGP) traits, including N-fixation, solubilisation of P, K, and Zn, as well as IAA and exopolysaccharide production, revealed significant differences. Rhizobium pusense strain MB4 and Sphingobium spp. strain MB6 were best in terms of both PGP traits and methanol use efficiency. This study suggests that these methylotrophs serve dual purpose of mitigation of methane carbon emission and can be used as promising candidates for enhancing crop growth.